Identification of Candidate Chemosensory Receptors in the Antennae of the Variegated Cutworm, Peridroma saucia Hübner, Based on a Transcriptome Analysis - Sun, Ya-Lan; Dong, Jun-Feng; Gu, Nan; Wang, Shao-Li (Frontiers in Physiology, 2020)
Insect chemoreception, including olfaction and gustation, involves several families of genes, including odorant receptors (ORs), ionotropic receptors (IRs), and gustatory receptors (GRs). The variegated cutworm Peridroma saucia Hübner (Lepidoptera: Noctuidae) is a worldwide agricultural pest that causes serious damage to many crops. To identify such olfactory and gustatory receptors in P. saucia, we performed a systematic analysis of the antennal transcriptome of adult P. saucia through Illumina sequencing. A total of 103 candidate chemosensory receptor genes were identified, including 63 putative ORs, 10 GRs, 24 IRs, and 6 ionotropic glutamate receptors (iGluRs). Phylogenetic relationships of these genes with those from other species were predicted, and specific chemosensory receptor genes were analyzed, including ORco, pheromone receptors (PRs), sugar receptors, CO2 receptors, and IR co-receptors. RT-qPCR analyses of these annotated genes revealed that 6 PRs were predominantly expressed in male antennae; 3 ORs, 1 GR, 2 IRs, and 2 iGluRs had higher expression levels in male than in female antennae; and 14 ORs, 1 GR, and 3 IRs had higher expression levels in female than in male antennae. This research increases the understanding of olfactory and gustatory systems in the antennae of P. saucia and facilitates the discovery of novel strategies for controlling this pest.